Association of Plasma Circulatory Markers, Chlamydia pneumoniae, and High Sensitive C-Reactive Protein in Coronary Artery Disease Patients of India - Hem Chandra Jha; Pragya Srivastava; Rakesh Sarkar; Jagdish Prasad; Aruna Singh Mittal (Mediators of Inflammation)
Plasma inflammatory markers have been shown to be predictors for cardiovascular risk, however, there is no study where the levels of plasma circulatory markers have been evaluated in coronary artery disease patients (CAD pts) positive for C. pneumoniae IgA and high sensitive C-reactive protein (hsCRP) which may help in better understanding of disease pathogenesis. A total of 192 patients and 192 controls attending the Cardiology Outpatient Department of Safdarjung Hospital were enrolled. The levels of plasma circulatory inflammatory markers were evaluated by ELISA. The levels of circulatory plasma markers (IL-4, IL-8, IL-13, ICAM-1, and VCAM-1) were significantly higher, whereas, levels of IL-10 and IFN-γ were significantly lower in CAD pts compared to healthy controls. The levels of IL-4, IL-8, and ICAM-1 (P=.007, .015, and .048) were significantly higher, however, IL-10 and IFN-γ were significantly lower (P<.001, <.001) in C. pneumoniae IgA positive CAD pts. The levels of IL-4, IL-8, IL-13, ICAM-1, and VCAM-1 were higher but not significant and levels of IL-10 and IFN-γ were significantly (P<.001, <.001) lower in hsCRP positive CAD pts. Our study suggested that circulatory cytokines, namely, IL-4, IL-8, and adhesive molecules like ICAM-1 were enhanced after infection with C. pneumoniae whereas in contrast to this IL-10 and IFN-λ